ANALYSIS OF THE SUPPLY OF RED CHILLI (Capsicum Annum. L) IN NORTH SUMATRA PROVINCE - Yayu Juita Agustina Tobing; Lindawati; Salmiah (CV. Radja Publika, 2024)
YAYU JUITA AGUSTINA TOBING (207039019) with the thesis title